Diaphragmatic Thickening Fraction by Ultrasound in Mechanically Ventilated Pediatric Patients: Pilot Observations During Spontaneous Breathing Trials. (7th June 2022) - Shah, Ami J.; Wai, Kitman; Sharron, Matthew P.; Mize, Marisa; Cohen, Joanna; Basu, Sonali
Abstract : Objectives: In critically ill, mechanically ventilated adults, diaphragmatic atrophy and reduced diaphragmatic thickening fraction (DTF) has been associated with poor extubation outcomes. Diaphragmatic ultrasound assessment in critically ill pediatric patients shows similar results, though studies are on‐going. We sought to explore the feasibility and utility of using DTF, obtained during a spontaneous breathing trial (SBT) in predicting weaning outcomes. Methods: We conducted a prospective, observational study in a single‐center tertiary noncardiac pediatric intensive care unit (PICU) in a children's hospital. Mechanically ventilated pediatric patients were included except for those with preexisting conditions of neuromuscular weakness, diaphragm paresis, or chronic respiratory failure requiring non‐invasive or invasive mechanical ventilation at baseline. A convenience sample of 38 patients were included in the study. Results: Weaning failure occurred in 10/38 (26%) instances with 9/38 (24%) occurring due to failed SBT and 1/38 (2%) due to failed extubation requiring reintubation. Median DTF was 24% (IQR: 12–33). DTF was significantly lower in instances of failed SBT, 12% compared to 27% ( P < .01). The odds ratio (OR) of SBT failure utilizing: TF < 25% is 12 (CI: 1.33–108.0, Z ‐score: 2.22, P = .027), TV <5 mL/kg was 10.4 (CI: 1.76–61.67, Z ‐score: 2.58, P = .01), and combined TV <5 mL/kg and TF < 25% is 17.6 (CI: 1.19–259.61, Z ‐score: 2.09, P = .04). Conclusions: Our preliminary study suggests that ultrasound measurements of diaphragm thickening fraction during spontaneous breaths in mechanically ventilated pediatric patients may be a useful addition in predicting weaning readiness.